Regression Analysis of ESG Ratings on Company Valuation and Financial Metrics - Chen, Yiyi; Helman, Karel; Malec, Lukáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis investigates the relationship between Environmental, Social, and Governance (ESG) component scores and company valuation and financial performance, focusing on China's A-share market with 1,443 companies observed over the period from 2012 to 2023, resulting in 17,316 total combinations of companies and years. The study employs various panel regression models, including pooled and fixed effects methodologies, to examine the paired and partial relationships between ESG components—environmental (E), social (S), and governance (G)—and valuation and performance indicators such as Tobin’s Q and return on assets (ROA). The findings indicate a generally negative paired and partial relationship between environmental scores and Tobin's Q and ROA. Conversely, a positive paired and partial relationship is indicated between social and governance scores and Tobin's Q and ROA. These results partially support the research hypotheses. Additionally, subgroup analyses based on industry and regional characteristics suggest that these factors may cause the relationship between ESG scores and company valuation and performance to vary.
Vedoucí práce: Karel Helman
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: data analysis and modeling [obor dipl. práce]; diplomové práce; master's theses